PENGGUNAAN IEKAD DALAM KONSELING KARIR UNTUK MEMBANTU SISWA MEMAHAMI PREFERENSI VOKASIONALNYA - Esti Yulistia Sumantri; Syarifuddin Dahlan; Ratna Widiastuti (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of this research was intended to determine, knowing the students’ potential in determining vocational preferences after given IEKAD. The problem in this study was that many students who have a difficulty in understanding the potential of vocational preferences. In this research, the researcher used quasi experimental method in which to insert the sample into the experimental group and the control group randamization. The design used was a non randomized pretest-posttest control group. This research was indicated by the difference between the posttest of experimental group with the posttest of control group, the average was 62.17% of the experimental group and the average was 52.08% of control group, it is meant that IEKAD could help to improve the students’ understanding of vocational preferences. The suggestions in this research proposed to (1) Teachers Advisors, suggested to the guidance counselor to help the students understanding the vocational preferences of the students, among others, could use IEKAD, (2) Other researchers, in this research, IEKAD in career counseling was not suitable for students who have low self esteem. (3) Students, the students were expected to follow the career counseling to help understanding the vocational preferences. Keywords: IEKAD, Career Counseling, Vocational Preferences.